P.071 Clinical and demographic predictors of stress in parents of children with genetically determined leukoencephalopathies. (5th June 2019) - Dermer, EA; Spahr, A; Tran, L; Mirchi, A; Pelletier, F; Guerrero, K; Bernard, G
Abstract : Background: Genetically-determined leukoencephalopathies comprise a rare group of inherited white matter disorders. The vast majority are associated with a progressive disease course and early death. This study seeks to determine the clinical and demographic correlates of stress in parents of leukodystrophy patients, for future clinical guidance.Methods: A cross-sectional study including 36 families was performed. Children aged 1 month to 12 years with a diagnosed leukodystrophy or genetically-determined leukoencephalopathy were included. 31 mothers and 24 fathers completed the Parental Stress Index, 4 th edition (PSI-4). One demographic questionnaire was completed per family. Clinical data was gathered within 6 months of the questionnaires. Statistical analysis was performed with total stress (TS) scores as the primary outcome.Results: Mothers and fathers had comparable TS scores. No clinical or demographic factors predicted the father's TS score. Greater ambulatory impairment, using the GMFCS scale, correlated to lower TS scores in the mother.Conclusions: The progressive nature of these conditions makes it such that anticipating a child's inability to walk may cause more stress for mothers than a child's actual inability to ambulate. The inability of all other variables to predict total stress highlights a need for individualized approaches when addressing stress in these families.